Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The example I'm doing gives an equation $$L(y, y') = \frac{y'}{y}$$

then $$\frac{\partial L}{\partial y} = -\frac{y'}{y^2}$$ and $$\frac{\partial L}{\partial y'} = \frac{1}{y}$$ ... $$\frac{d}{dx}\frac{\partial L}{\partial y'} = \frac{d}{dx}\frac{1}{y} = -\frac{y'}{y^2}$$

substituting into the Euler Lagrange $$\frac{\partial L}{\partial y} = \frac{d}{dx} \frac{\partial L}{\partial y'}$$ then yields $$-\frac{y'}{y^2} = -\frac{y'}{y^2}$$

Does this mean that any differentiable function $y$ is a solution to the Euler-Lagrange equation for that Lagrangian??

share|cite|improve this question
up vote 7 down vote accepted

The reason is that $$ \mathcal{L}=\int_a^b L\big(y(t),y'(t)\big)\,dt =\int_a^b\frac{y'(t)}{y(t)}\,dt=\big[\ln y(t)\big]_a^b=\ln y(b)-\ln y(a) $$ is independent of the path, and hence, all paths are stationary.

share|cite|improve this answer
    
very good... thanks a lot – Ronald Sep 6 '12 at 15:21

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.